2014
DOI: 10.1103/physreva.90.022504
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of density-functional approximations for light atoms in strong magnetic fields

Abstract: For a wide range of magnetic fields, 0 B 2000 a.u., we present a systematic comparative study of the performance of different types of density-functional approximations in light atoms (2 Z 6). Local, generalized-gradient approximation (GGA; semilocal), and meta-GGA ground-state exchange-correlation (xc) functionals are compared on an equal footing with exact-exchange, Hartree-Fock (HF), and current-densityfunctional-theory (CDFT) approximations. Comparison also is made with published quantum Monte Carlo data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 85 publications
1
41
1
Order By: Relevance
“…Higuchi and Higuchi 33 (HH) have also presented a vorticity dependent form, derived to obey known exact relations for the CDFT exchange-correlation functional. Whilst the vorticity is a theoretically convenient choice to ensure the gauge invariance of the exchange-correlation energy it has been observed that in practical self-consistent calculations it can lead to significant numerical stability issues 16,17 . How severe these issues are depends on the exact parameterization of the the functional form, however, in all cases some degree of numerical regularization is required to ensure that the self-consistent field solution of the Kohn-Sham equations can be obtained.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Higuchi and Higuchi 33 (HH) have also presented a vorticity dependent form, derived to obey known exact relations for the CDFT exchange-correlation functional. Whilst the vorticity is a theoretically convenient choice to ensure the gauge invariance of the exchange-correlation energy it has been observed that in practical self-consistent calculations it can lead to significant numerical stability issues 16,17 . How severe these issues are depends on the exact parameterization of the the functional form, however, in all cases some degree of numerical regularization is required to ensure that the self-consistent field solution of the Kohn-Sham equations can be obtained.…”
Section: Theorymentioning
confidence: 99%
“…The KS orbitals are defined to minimize the non-interacting kinetic energy and yield the physical electronic density via Eq. (16). They also have appealing properties; for example the highest occupied MO energy is minus the first ionization potential (IP) 49,50 and the remaining orbital energies can be interpreted as Koopman's type approximations to higher IPs 51 .…”
Section: Interpretation Of Paramagnetic Bonding In the Ks-cdft Framentioning
confidence: 99%
“…Additionally, there is a great interest to formulate a density-functional theory (DFT) that properly takes into account the interaction with magnetic fields. [14][15][16][17][18][19][20] For these approaches, it is mandatory to have benchmark values to assess the quality of the results and help to construct improved functionals.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, practical experience with available approximate paramagnetic CDFT functionals has shown that vorticity is a numerically difficult quantity to work with [44][45][46]. A formulation in terms of physical currents is therefore an interesting alternative avenue to explore in the construction of practical density-functional approximations.…”
Section: Discussionmentioning
confidence: 99%